The Mass Political Economy of Capital Controls. (September 2019) - Steinberg, David A.; Nelson, Stephen C.
This article examines mass public opinion toward international financial-market regulations, known as "capital controls." Conventional wisdom maintains that most voters do not pay attention to or care about capital controls, but no previous studies have directly evaluated this claim. We argue that capital controls are likely to become a publicly salient issue under some conditions—specifically, when economically unstable countries reimpose regulations on capital outflows. Original data from two surveys fielded in Argentina support this argument. We show that most citizens are knowledgeable about capital controls, many consider it an important issue, individuals' preferences reflect their economic self-interest, and attitudes toward capital controls influenced vote choice in a presidential election. These results, along with illustrative evidence from four other cases, indicate that ostensibly complex policy issues such as international financial regulation can become electorally salient under some conditions.